2018
DOI: 10.1177/0020872818774111
|View full text |Cite
|
Sign up to set email alerts
|

Sexual exploitation of adolescent students in Tanzania: Implication for social services

Abstract: A considerable empirical research has been conducted on sexual exploitation of children and adolescents; however, limited information is available in developing countries. This study describes and discusses the prevalence, nature and characteristics of sexual exploitation of adolescents using data collected from 1116 secondary school students in Tanzania. Results indicate that 21 percent of the surveyed adolescent students had had at least one experience of sexual exploitation. Being a female, living in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Sexual coercion presented a noteworthy prevalence in the reviewed papers addressing the topic. A study published after our review process was terminated and conducted in Tanzania reported a similar prevalence of sexual coercion among boys and girls (21%) [30]. Our data also stressed the high risk of sex coercion associated with girls, those who usually experience more vulnerable conditions.…”
Section: Discussionsupporting
confidence: 72%
“…Sexual coercion presented a noteworthy prevalence in the reviewed papers addressing the topic. A study published after our review process was terminated and conducted in Tanzania reported a similar prevalence of sexual coercion among boys and girls (21%) [30]. Our data also stressed the high risk of sex coercion associated with girls, those who usually experience more vulnerable conditions.…”
Section: Discussionsupporting
confidence: 72%
“…In terms of gender enrollment, Tanzania has attained gender parity in primary school enrollment and near parity in lower secondary enrollment. But the performance of boys in the primary school leaving examination still dwarfs that of girls (Mlyakado, 2012). Again, a contrast can be drawn here between Tanzania and Kenya, which recently does not exhibit systematic gender pattern in the cadre of top performing students in primary school leaving exams.…”
Section: Attention To Culturementioning
confidence: 65%
“…Limited access increases the risk of, for example, unplanned pregnancy and STIs among adolescents [ 18 ]. What adds to the urgency for SRH services is the socially normalised sexual exploitation of adolescents in Tanzania [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%